2007
DOI: 10.1111/j.1440-1746.2007.05031.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of human gastric cell lines with stem cell phenotypes

Abstract: The new cell culture method can be used to develop gastric epithelial cell clones with sustained growth from endoscopic biopsy. The gastric cell clone showed several stem and/or progenitor cell phenotypes (i.e. the ability of AIG, high differentiation capacity, high susceptibility to spontaneous immortalization and the expression of Oct-4). The telomerase expression in these gastric stem and/or progenitor cells can be upregulated by exposure to H. pylori culture products and MNNG, an important step in neoplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 32 publications
(66 reference statements)
1
38
0
Order By: Relevance
“…The results showed that CS12 were more resistant to 5-fluorouracil than CSN cells (Figure 1E). Their in vivo tumorigenicity was examined using a xenograft transplantation test and only CS12 cells generated tumors in SCID mice (Figure 1F) consistent with previous findings [30, 31]. The tumor showed 10% malignant cells that contained little cytoplasm (Supplementary Figure 1B).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The results showed that CS12 were more resistant to 5-fluorouracil than CSN cells (Figure 1E). Their in vivo tumorigenicity was examined using a xenograft transplantation test and only CS12 cells generated tumors in SCID mice (Figure 1F) consistent with previous findings [30, 31]. The tumor showed 10% malignant cells that contained little cytoplasm (Supplementary Figure 1B).…”
Section: Resultssupporting
confidence: 85%
“…Both CS12 and CSN cells express OCT4 stemness genes [30, 31]. Here, we further characterized whether CS12 possessed typical stem cell features.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Growth factors, hormones, extracellular matrix, and cytokines can also block GJIC [38]. In many AS cells, neither the connexin genes are expressed nor are the gap junctions functional [39]. The cancer cells completely lose expression of connexin gene.…”
Section: Fig 5: Es Cell Derived Differentiation-related Endpoints Usmentioning
confidence: 99%